1979
DOI: 10.1111/j.1600-0722.1979.tb00706.x
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscopic study of the effect of various cleansing agents on cavity walls in vitro

Abstract: – The appearance of prepared cavity walls after treatment with different cavity cleansers and cleaning procedures was studied. Class II and V cavities were prepared on extracted human and monkey teeth and the cavities were exposed to the different agents for 1 min. Where commercial products were used, the manufacturers' directions for use were followed. The cavity walls were examined in the scanning electron microscope and representative photos were taken from dentinal and enamel areas. Only demineralizing so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
3
19
0
1
Order By: Relevance
“…The depth was also significantly less when the cavities restored with microfilled resin had been cleaned with Tubulicid than when they had been cleaned with water. Since both Tubulicid and citric acid have the capacity to remove the smear layer of debris from cavity walls (Leidal and Eriksen, 1979;Brinnstr6m et al, 1980), it appears from the analysis of the lesion depths that one of the important features in the reduction of lesion depth is the removal of the smear layer.…”
Section: Resultsmentioning
confidence: 98%
“…The depth was also significantly less when the cavities restored with microfilled resin had been cleaned with Tubulicid than when they had been cleaned with water. Since both Tubulicid and citric acid have the capacity to remove the smear layer of debris from cavity walls (Leidal and Eriksen, 1979;Brinnstr6m et al, 1980), it appears from the analysis of the lesion depths that one of the important features in the reduction of lesion depth is the removal of the smear layer.…”
Section: Resultsmentioning
confidence: 98%
“…75 A further consideration is that 30 per cent hydrogen peroxide treatment of dentine may elicit a pulpal response by altering the extent of microleakage around a composite resin restoration. 76 …”
Section: Dental Pulpmentioning
confidence: 99%
“…It appears that procedures employed in normal cavity toilet such as the use of water-spray and hydrogen peroxide do not remove the smear layer and that only demineralizing solutions are able to perform this (6,7). Several of these are currendy marketed including phosphoric, polyacrylic and citric acids and EDTA-based solutions.…”
mentioning
confidence: 99%
“…Much controversy exists over the depth to which these conditioning agents penetrate the residual dentin and whether they injure the underlying pulp (6,(11)(12). Retief (13) has reported a severe reaction to phosphoric acid conditioner in monkeys and Macko et al (4) in humans, while Mjor et al (16) have reported little response to a variety of acids in the same animal.…”
mentioning
confidence: 99%
See 1 more Smart Citation